Pelestarian Candi Gumpung Sebagai Benda Cagar Budaya dan Pariwisata di Provinsi Jambi - Pratama, Tito Satria; Mubarok, Basri Al; Faroby, A. Izzat Al; Atika, Atika; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Gumpung Temple, as one of the historical sites of the Muaro Jambi Temple Complex, has an important value as a cultural heritage object that reflects the glory of past civilization in Jambi Province. This study aims to analyze the efforts to preserve Gumpung Temple from the perspective of cultural heritage and its potential as a tourism destination. The research method used is descriptive qualitative with a field study approach, in-depth interviews with related parties, and secondary data analysis. The results of the study indicate that efforts to preserve the temple face several challenges, such as structural damage due to natural factors, lack of awareness of the surrounding community, and limited funds and experts in restoration. However, the local government, in collaboration with the Cultural Heritage Conservation Center (BPCB), has implemented various programs such as periodic restoration, educational activities for the community and students, and promotion of culture-based tourism. Management of tourism based on cultural preservation is also one of the main strategies to make Gumpung Temple a leading tourist attraction, while maintaining conservation aspects. The results of this study also emphasize the importance of collaboration between the government, community, and private sector in supporting the sustainability of the preservation of this cultural heritage. In addition, the determination of Gumpung Temple as part of the world heritage site by UNESCO can be a strategic step to increase national and international attention to the preservation and development of culture-based tourism in Jambi Province. This study concludes that the preservation of Gumpung Temple as a cultural heritage object and tourism destination requires a holistic approach that integrates aspects of conservation, education, and empowerment of the local community economy. Thus, Gumpung Temple not only functions as a historical heritage but also as a tourism asset that provides sustainable economic and social benefits.